A comparative technoeconomic analysis of renewable hydrogen production using solar energy. Issue 7 (26th May 2016) - Shaner, Matthew R.; Atwater, Harry A.; Lewis, Nathan S.; McFarland, Eric W.
Abstract : Solar H2 production cost ($ kg −1 ) techno-economic landscape for photoelectrochemical (PEC) and photovoltaic-electrolysis (PV-E). References include conventional H2 production, robust outdoor material (artificial grass) and solar cell. Abstract : A technoeconomic analysis of photoelectrochemical (PEC) and photovoltaic-electrolytic (PV-E) solar-hydrogen production of 10 000 kg H2 day −1 (3.65 kilotons per year) was performed to assess the economics of each technology, and to provide a basis for comparison between these technologies as well as within the broader energy landscape. Two PEC systems, differentiated primarily by the extent of solar concentration (unconcentrated and 10× concentrated) and two PV-E systems, differentiated by the degree of grid connectivity (unconnected and grid supplemented), were analyzed. In each case, a base-case system that used established designs and materials was compared to prospective systems that might be envisioned and developed in the future with the goal of achieving substantially lower overall system costs. With identical overall plant efficiencies of 9.8%, the unconcentrated PEC and non-grid connected PV-E system base-case capital expenses for the rated capacity of 3.65 kilotons H2 per year were $205 MM ($293 per m 2 of solar collection area (mS −2 ), $14.7 WH2, P −1 ) and $260 MM ($371 mS −2, $18.8 WH2, P −1 ), respectively. The untaxed, plant-gate levelized costs for the hydrogen product (LCH) were $11.4 kg −1 and $12.1 kg −1 for the base-case PEC and PV-E systems, respectively. The 10× concentrated PEC base-case system capital cost was $160 MM ($428 mS −2, $11.5 WH2, P −1 ) and for an efficiency of 20% the LCH was $9.2 kg −1 . Likewise, the grid supplemented base-case PV-E system capital cost was $66 MM ($441 mS −2, $11.5 WH2, P −1 ), and with solar-to-hydrogen and grid electrolysis system efficiencies of 9.8% and 61%, respectively, the LCH was $6.1 kg −1 . As a benchmark, a proton-exchange membrane (PEM) based grid-connected electrolysis system was analyzed. Assuming a system efficiency of 61% and a grid electricity cost of $0.07 kWh −1, the LCH was $5.5 kg −1 . A sensitivity analysis indicated that, relative to the base-case, increases in the system efficiency could effect the greatest cost reductions for all systems, due to the areal dependencies of many of the components. The balance-of-systems (BoS) costs were the largest factor in differentiating the PEC and PV-E systems. No single or combination of technical advancements based on currently demonstrated technology can provide sufficient cost reductions to allow solar hydrogen to directly compete on a levelized cost basis with hydrogen produced from fossil energy. Specifically, a cost of CO2 greater than ∼$800 (ton CO2 ) −1 was estimated to be necessary for base-case PEC hydrogen to reach price parity with hydrogen derived from steam reforming of methane priced at $12 GJ −1 ($1.39 (kg H2 ) −1 ). A comparison with low CO2 and CO2 -neutral energy sources indicated that base-case PEC hydrogen is not currently cost-competitive with electrolysis using electricity supplied by nuclear power or from fossil-fuels in conjunction with carbon capture and storage. Solar electricity production and storage using either batteries or PEC hydrogen technologies are currently an order of magnitude greater in cost than electricity prices with no clear advantage to either battery or hydrogen storage as of yet. Significant advances in PEC technology performance and system cost reductions are necessary to enable cost-effective PEC-derived solar hydrogen for use in scalable grid-storage applications as well as for use as a chemical feedstock precursor to CO2 -neutral high energy-density transportation fuels. Hence such applications are an opportunity for foundational research to contribute to the development of disruptive approaches to solar fuels generation systems that can offer higher performance at much lower cost than is provided by current embodiments of solar fuels generators. Efforts to directly reduce CO2 photoelectrochemically or electrochemically could potentially produce products with higher value than hydrogen, but many, as yet unmet, challenges include catalytic efficiency and selectivity, and CO2 mass transport rates and feedstock cost. Major breakthroughs are required to obtain viable economic costs for solar hydrogen production, but the barriers to achieve cost-competitiveness with existing large-scale thermochemical processes for CO2 reduction are even greater.